Tuberculosis and Pregnancy - Rodríguez, Fernando (2015)
We have presented to the II Peruvian Congress of Obstetrics and Gynecology, a study on the evolution of pulmonary tuberculosis in connection with pregnancy, in a group of 294 sick, we could follow personally. The influence they can have on their degree of lesion development activity, the quality and extent of it, all of which have demonstrated a role of importance in the overall result was considered. All our patients underwent therapeutic regimens of modern antibiotics, and some of them also turned 01 pneumothorax, frenoparálisis and thoracoplasty. The influence that could have the number of pregnancies was also studied. Delivery in our patients was resolved according to obstetric conditions of the moment. Postpartum only we take into consideration infectious processes. 105 children study their weight and perinatal mortality.